OPTIMALISASI PEMBUATAN BROWNIES IKAN GABUS - Tri Marta Fadhilah (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Cork fish contains a lot of albumin compared to other freshwater fish, male cork fish albumin content of 6,7%, lower than female cork fish that have albumin 8,2%, are general brownies are made from flour, however, some have added fish to making brownies such as catfish and tilapia, but no one has added cork fish to make brownies, this study aims to determine to difference in sensory characteristics, the quality and content of albumin as well as the community's acceptance of brownie products. The design of this research is descriptive experimental design consisting of 2 factors: the proportion of the addition of cork fish consisting of 3 levels (60 grams, 80 grams, 100 grams), with the cork steaming process and the process without steaming cork fish. The results of this study are the average characteristics of brown, not fish-scented, not fishy and soft-textured. Brownie products that have significant differences both in terms of color, aroma, taste and texture are brownie samples with the addition of 100 grams of raw and 100 grams of steamed. The albumin content test for the addition of cork fish brownies which had the highest albumin content was found in the 100 gram raw cork fish addition brownie sample that was equal to 459.29% w / w. The results of the quality of brownie products are in accordance with SNI with the quality of water content <40% and ash content <3%. The acceptance of brownie products is that most people choose brownies with the addition of steamed cork 60 grams. The conclusion is cork fish brownies are acceptable to the public and contain high albumin.